Analysis of Self-Efficacy and Mental Toughness on Peak Performance in U-16 Football Athletes of Koni, Bekasi City - Angelina Hutomo (CV. Publikasi Indonesia, 2025)
This research explores the influence of self-efficacy and mental toughness on the peak performance of U-16 football athletes from KONI Bekasi City. The research addresses the problem of inconsistent performance among young athletes, often attributed to a lack of psychological readiness, such as confidence and resilience. The objective of this study is to examine the extent to which these psychological factors contribute to peak performance. Using a quantitative research method, data were collected from 21 athletes aged 12–16 years through Likert-scale instruments tailored to measure self-efficacy, mental toughness, and peak performance. The results reveal significant positive correlations: self-efficacy influences peak performance with a correlation of r = 0.943, while mental toughness has a correlation of r = 0.940. Together, these factors explain 97% of the variance in peak performance (r = 0.985). This research highlights the critical role of self-efficacy and mental toughness in optimizing athletic performance, emphasizing the need for early psychological development in athletes. The findings provide valuable insights for coaches and sports institutions to design training programs that enhance both mental and physical preparation.